2010
DOI: 10.1152/japplphysiol.00147.2010
|View full text |Cite
|
Sign up to set email alerts
|

Airway distensibility and volume recruitment with lung inflation in COPD

Abstract: The effects of full lung inflation on respiratory conductance (Grs) and reactance (Xrs) were measured in 15 subjects with moderate to severe chronic obstructive pulmonary disease (COPD) and 11 matched healthy control subjects. Airway distensibility was estimated from the ratio of the difference of Grs between functional residual capacity and total lung capacity to the relevant changes in lung volume (ΔGrs/ΔVl) or transpulmonary pressure (ΔGrs/ΔPtp). Similar analysis was applied to Xrs to estimate lung volume r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…These data suggest that airflow limitation and/or airway collapse are less common in patients with the lowest airway elastic fibres content. One may speculate that lowered elastic fibres content reduces airway wall compliance thereby increasing airway wall stiffness, which indeed has been observed in COPD [33] and even in asthma [34]. Hence, in the presence of COPD lowered airway elastic fibres content may even represent a protective mechanism against airflow limitation.…”
Section: Discussionmentioning
confidence: 86%
“…These data suggest that airflow limitation and/or airway collapse are less common in patients with the lowest airway elastic fibres content. One may speculate that lowered elastic fibres content reduces airway wall compliance thereby increasing airway wall stiffness, which indeed has been observed in COPD [33] and even in asthma [34]. Hence, in the presence of COPD lowered airway elastic fibres content may even represent a protective mechanism against airflow limitation.…”
Section: Discussionmentioning
confidence: 86%
“…As published previously, we believe that this decrease in distensibility is due to a combination of intrinsic remodeling of the airway walls and progressive parenchymal destruction. 11,15 We extended this knowledge by demonstrating that the association between emphysema and global airway distensibility remained after adjustment for relevant covariates, such age and sex. We believe that this adjustment is important because studies have shown differences in airway diameter changes with lung infl ation by sex and age in healthy lungs 24 and by age in diseased lungs.…”
Section: Airway Distensibility Across Groupsmentioning
confidence: 78%
“…In fact, Baldi et al 15 demonstrated the relationship between emphysema and distensibility only after albuterol administration. Similarly, we validated this association in the postbronchodilator cohort (e- Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control group exhibited little variation (fig. 4); this was most likely associated with a physiological response involving the airway epithelium, nerves, mediators and bronchial smooth muscle [6,10,37]. The greater (fig.…”
Section: Impedance Modulusmentioning
confidence: 99%